The Comparison Between Ad Valorem and Specific Taxation under Imperfect Competition - Sofia Delipalla; Michael Keen (Queen's University, Department of Economics, 1991)
This paper compares ad valorem and specific taxation in two models of oligopoly, with and without free entry. Predominantly ad valorem taxation implies a relative low consumer price, high tax revenue and (when entry is precluded) low profits. Ad valorem taxation dominates specific from the welfare perspective: the set of circumstances under which (with free entry) specific taxation raises welfare is a strict subset of that in which ad valorem taxation is welfare-improving, and in both models the maximization of consumer welfare subject to a binding revenue constraint requires maximum reliance on ad valorem taxation.
Keywords: 330